Hubungan Pengetahuan Dan Sikap Terhadap Praktek Pemilahan Sampah Padat Medis Oleh Tenaga Kesehatan di UPT Puskesmas Bonti - Linda; Dewi Rosita Pasaribu; Fahmi Fuadah (Institut Kesehatan Immanuel, 2025)
Community health centers (Puskesmas) are health care facilities that are obligated to manage their waste, both medical and non-medical, which is the responsibility of health workers. This study aims to analyze the correlation between the knowledge and attitudes of health workers and the practice of sorting medical solid waste at the Bonti Community Health Center (UPT). This study is a descriptive correlational study using a cross-sectional study approach. This study involved all health workers at the Bonti Community Health Center (UPT) as a population of 34 people, with a total sample being used as the sampling technique. The research instrument was a questionnaire to measure knowledge and attitudes, and an observation sheet to measure the practice of sorting medical solid waste. Data analysis was conducted using the chi-square test. This study found that 55.9% of health workers had good knowledge and 44.1% had poor knowledge. 58.8% of health workers had positive attitudes, while 41.2% had negative attitudes. Meanwhile, the practice of sorting medical solid waste showed that 52.9% of health workers had good practices and 47.1% had poor practices. Analysis using the Chi-Square test revealed a significant correlation between knowledge and practice (p=0.042) and attitude and practice (p=0.017). It is recommended that Community Health Centers (Puskesmas) periodically monitor medical solid waste sorting practices to ensure that all healthcare workers sort medical solid waste according to standards.